Experimental assessment of damage and microplastic release during cyclic loading of clear aligners - Claudia Barile; Claudia Cianci; Vimalathithan Paramsamy Kannan; Giovanni Pappalettera; Carmine Pappalettere; Caterina Casavola; Michele Laurenziello; Domenico Ciavarella (PLoS ONE, 2025)
The widespread adoption of clear aligners in orthodontic treatments in recent years has necessitated a more precise examination of the mechanical properties of the devices currently available in orthodontics. Recent studies indicate that aligners, when exposed to the forces exerted during swallowing, undergo fatigue-like phenomena, leading to chip formation and cracks. The cumulative damage results in a compromised fit between the tooth and aligner, which is crucial for the effective execution of orthodontic treatment. Additionally, the formation of chips poses a potential risk to patients, as there is a possibility of inadvertently ingesting microplastics that become detached from the aligner over time. This study attempts to assess the release of microplastics from the aligners subjected to cyclic compressive loading. Three different aligners (Essix Ace, Ghost Aligner and Invisalign) are tested to simulate swallowing conditions over the aligner usage period. The mechanical performance is studied in terms of the energy absorbed by the aligner, which shows that the Essix Ace has a stable energy absorption behaviour, while the energy absorbed by the Invisalign is significantly higher than their counterparts. Ghost Aligner did not perform well in the cyclic compression tests. The microplastics (MPs) released by the aligners are examined under an optical microscope. A dimensional analysis based on k-means image segmentation and edge detection algorithm is developed to analyse the MPs. The dimensional analysis of the MPs revealed that the ingestion of the MPs released by all the three aligners does not pose a health risk.